What do you mean by love? Understanding brand love experiences - Sutil, Bruno do Nascimento (2019)
This study proposes that brand love is an umbrella term for different brand love experiences and proposes a scale to differentiate among them. After a literature review and a qualitative stage, reasons to love a brand were coded based on the relationship experiences the interviewees have with their loved brands. Each of the codes were translated into sentences, and a sample of 327 brand lovers were asked to choose their degree of agreement to each of the sentences. Through factorial analysis and Structural Equation Modeling (SEM) five factors emerged, representing brand love experiences, based on the grouping of reasons to love a brand: Values, Status, Involvement, Benefits and Quality, which exhibit distinct relationships to the long-established antecedents and consequents of brand love.